2013
DOI: 10.1371/journal.pone.0072106
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Gut Diversity of Africanized and European Honey Bee Larval Instars

Abstract: The first step in understanding gut microbial ecology is determining the presence and potential niche breadth of associated microbes. While the core gut bacteria of adult honey bees is becoming increasingly apparent, there is very little and inconsistent information concerning symbiotic bacterial communities in honey bee larvae. The larval gut is the target of highly pathogenic bacteria and fungi, highlighting the need to understand interactions between typical larval gut flora, nutrition and disease progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
180
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(189 citation statements)
references
References 57 publications
9
180
0
Order By: Relevance
“…This was certainly possible for bees from the field study but more difficult for those from the cage studies, since they were collected at the L5 stage and transferred to the lab until eclosion and sampled immediately after, in the case of newly emerged bees, or maintained in cages until sampling, in the case of adult bees. However, it has been shown that L5 larvae can harbor bacteria from the family Neisseriaceae (Vojvodic et al, 2013). Our results suggest that the presence of the mite may serve to spread the bacteria from the shed integument and gut intima within the cell, thereby more readily contaminating the emerging adult bee before eclosion.…”
Section: Resultsmentioning
confidence: 77%
“…This was certainly possible for bees from the field study but more difficult for those from the cage studies, since they were collected at the L5 stage and transferred to the lab until eclosion and sampled immediately after, in the case of newly emerged bees, or maintained in cages until sampling, in the case of adult bees. However, it has been shown that L5 larvae can harbor bacteria from the family Neisseriaceae (Vojvodic et al, 2013). Our results suggest that the presence of the mite may serve to spread the bacteria from the shed integument and gut intima within the cell, thereby more readily contaminating the emerging adult bee before eclosion.…”
Section: Resultsmentioning
confidence: 77%
“…The results with Fructobacillus F2 supernatant recapitulated a subset of the results from Fructobacillus F2 cocultures; Fructobacillus F2 supernatant had a similar, positive effect on growth of Bifido G10-2, Firm-4 SF6D, Firm-5 D7-1, and Bifido B08 compared to growth of these isolates alone. Because Firm-5 species are known to associate with second-instar honey bee larvae (24) and therefore are present early in development, we further characterized the potential interaction between a Firm-5 strain (Firm-5 D7-1) and Fructobacillus F2. Spent medium from Fructobacillus F2 significantly increased the differential optical density reached by Firm-5 compared to growth in MRS alone based on both the optical density and the CFU (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria that comprise the lactic acid bacteria are not a phylogenetically cohesive designation, based on 16S rRNA evolution, but instead are grouped based on common metabolic characteristics, including the production of lactic acid through fermentative metabolism. Within the honey bee, several different LAB clades have been found associated with the hymenopteran host through culture, clone library sequencing, or amplicon-based sequencing (3,7,24). Some of these LAB clades are described as part of the core honey bee microbiome and include Firm-4, Firm-5, and Bifido.…”
Section: Discussionmentioning
confidence: 99%
“…In the second experiment, we observed a large number of non-core bacteria, particularly P. apium , non-Firm 4 and Firm 5 Lactobacillus sp., Enterococcaceae , and the pathogen P. larvae . P. apium is found at lower levels in the gut (Corby-Harris et al 2014a;Martinson et al 2011;Martinson et al 2012;Moran et al 2012;Sabree et al 2012) and is typically more abundant in hive food stores (Anderson et al 2014), queens (Kapheim et al 2015;Tarpy et al 2015), larvae (Vojvodic et al 2013), and in the hypopharyngeal glands and crops of nurses (Corby-Harris et al 2014b). Because P. apium is relatively abundant in food stores, hypopharyngeal glands, and crop, one possibility is that the guts displaying high P. apium titers were recently inoculated through either pollen feeding or trophallaxis.…”
Section: Discussionmentioning
confidence: 99%